Application of Critical Chain Project Management on Engine Maintenance at PT. Rekatama Putra Gegana Aviation - Raga, Ridha Azka; Pertiwi, Husna Putri; Jasrial, Jasrial (Yayasan Ilomata, 2024)
Planning is a crucial element for aircraft maintenance companies to achieve higher profitability. However, in practice, the company still employs traditional planning methods, which are deemed inefficient as they do not consider the productivity of each task involved, leading to issues arising from human behavior tendencies causing additional time for task completion. Aircraft maintenance planning can be improved by employing the Critical Chain Project Management (CCPM) method, which offers a different approach to determining the time and cost of aircraft maintenance. This method addresses multitasking, student syndrome, Parkinson's law, and provides buffers at the end of tasks. Analysis results show that the completion time for tasks within the company, totaling 76 days, differs by 14 days compared to the completion time using the CCPM method, which is 62 days. This indicates that employing the CCPM method for engine maintenance is more effective and efficient. The efficiency achieved amounts to Rp7,036,323.